Anti-cracking agent for lithium ion battery as well as preparation method and application of anti-cracking agent

By modifying the anti-cracking agent composed of polyvinyl butyral and triblock polymer, the problem of prone to cracking of lithium-ion battery pole plates under high energy density is solved, and the integrity of the battery pole plates and the battery performance is improved.

CN119875131APending Publication Date: 2025-04-25JIANGXI INSPIRE NANO MATERIALS CO LTD

Patent Information

Application Number
CN202510086626.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-19
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the process of increasing the volume energy density and mass energy density of existing lithium-ion batteries, the extreme sheets are prone to become brittle and cracking, resulting in a decrease in energy density and poor battery performance.

Method used

A lithium-ion battery anti-cracking agent is used, which consists of modified polyvinyl butyral and triblock polymer. By dissolving and reacting under nitrogen protection, an anti-cracking agent with high flexibility and thermal stability is formed.

Benefits of technology

At a low addition amount, the battery electrode sheet can be kept intact and not cracked under high surface density, maintain excellent battery performance, and meet the needs of high-energy-density lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250305890000022
    Figure BDA0005250305890000022
  • Figure BDA0005250305890000051
    Figure BDA0005250305890000051
  • Figure BDA0005250305890000052
    Figure BDA0005250305890000052
Patent Text Reader

Abstract

The invention discloses a lithium ion battery anti-cracking agent and a preparation method and application thereof.The preparation method is carried out under nitrogen protection and comprises the steps that a first polymer, a second polymer and a modifier are dissolved in a first solvent, and under the action of a catalyst, a reaction is carried out for 4-48 h at the temperature of 60-100 DEG C; and after the reaction is finished, cooling to below 40 DEG C, adding an amine compound, and reacting for 0.5-8 hours to obtain the anti-cracking agent for the lithium ion battery. The first polymer is polyvinyl butyral, and the hydroxyl content of the polyvinyl butyral is 18-21%; the second polymer is a triblock polymer as shown in a structural formula I, and the content of methyl methacrylate in the second polymer is 8-65%; the modifier is maleic anhydride or a maleic anhydride derivative; the catalyst is one of p-toluenesulfonic acid, hydrochloric acid and sulfuric acid. According to the anti-cracking agent, the battery pole piece can be intact and does not crack at high surface density under the condition of relatively low addition amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery anti-cracking agent and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries still face challenges such as high energy density, long cycle, safety and economy. One of the main directions to solve the problem is to improve the volume energy density and mass energy density of lithium-ion batteries, that is, to require the smallest battery pack to be able to coat more positive and negative electrodes, that is, to increase the thickness of the electrode sheet to achieve a single-sided density of 200g / m 2 .

[0003] PVDF is a commonly used binder for lithium-ion batteries. However, using only PVDF cannot meet the requirements of high surface density batteries. Adding a large amount of PVDF binder will lead to a series of problems such as decreased energy density, high viscosity of battery slurry, brittle electrode plates, and cracking. Summary of the invention

[0004] Based on this, the present application provides a lithium-ion battery anti-cracking agent, which can keep the battery pole pieces intact and crack-free at high surface density at a relatively low addition amount, thereby maintaining excellent battery performance.

[0005] A method for preparing a lithium ion battery anti-cracking agent, comprising:

[0006] Step 1, dissolving the first polymer, the second polymer and the modifier in the first solvent, reacting at 60-100° C. for 4-48 hours under the action of a catalyst;

[0007] Step 2, after the reaction in step 1 is completed, the temperature is lowered to below 40° C., an amine compound is added, and the reaction is carried out for 0.5 to 8 hours to obtain the lithium ion battery anti-cracking agent;

[0008] The first polymer is polyvinyl butyral, and the hydroxyl content (mass percentage) of the polyvinyl butyral is 18-21%;

[0009] The second polymer is a triblock polymer as shown in structural formula I, and the content of methyl methacrylate in the second polymer is 8% to 65%;

[0010] Structural formula Ⅰ

[0011] The modifier is maleic anhydride or a maleic anhydride derivative;

[0012] The catalyst is one of p-toluenesulfonic acid, hydrochloric acid and sulfuric acid.

[0013] The first polymer is polyvinyl butyral (PVB), which is the product of the condensation reaction of polyvinyl alcohol (PVA) and butyraldehyde in an acidic environment. Polyvinyl butyral contains three functional groups, namely butyral group, alcohol hydroxyl group and acetate group. The alcohol hydroxyl group and acetate group both come from polyvinyl alcohol. The hydroxyl group in the alcohol will not be completely acetalized to bring about alcohol hydroxyl group. Polyvinyl alcohol is generated by the hydrolysis of polyvinyl acetate. The incompletely hydrolyzed polyvinyl acetate brings about acetate group. The butyral group is formed by the condensation of polyvinyl alcohol and butyraldehyde.

[0014] The first polymer has a low glass transition temperature, good flexibility and strong adhesion, and is often used in safety glass interlayers. However, polyvinyl butyral has poor thermal stability, begins to decompose at 100°C, and swells in the electrolyte. Directly adding it to the positive electrode slurry of lithium-ion batteries may produce gas. In addition, polyvinyl butyral has a low molecular weight and is very prone to electrode brittle cracking.

[0015] In order to improve the thermal stability of the first polymer, the first polymer is modified by a modifier, and the reaction mechanism of the modification is as follows:

[0016]

[0017] The content of acetate structural units in the polyvinyl butyral is less than 4%.

[0018] Maleic anhydride and its derivatives have a high melting point and good solubility. The modified first polymer has good solubility and thermal stability in the first solvent. The modified first polymer can be used in a 4.5V high voltage system and in a lithium-ion battery without any safety hazard.

[0019] In addition, maleic anhydride and its derivatives contain abundant carbon-carbon double bonds in their molecular structure, which can form intermolecular conjugated large π bonds with the positive electrode materials of lithium-ion batteries. This can not only improve the dispersion of the first polymer in the positive electrode materials of lithium-ion batteries, but also provide migration and transmission channels for lithium ions, thereby improving the charge and discharge rate and efficiency of lithium batteries.

[0020] The second polymer is a triblock polymer having a flexible polybutyl acrylate soft segment, and both ends of the polybutyl acrylate are relatively rigid polymethyl methacrylate hard segments. The second polymer has a soft segment and a hard segment, which can improve the flexibility and thermal stability of the electrode plate.

[0021] The second polymer contains polar functional groups, which have better compatibility with other substances in the positive electrode slurry. The second polymer has good dispersibility in the positive electrode slurry. The soft segment in the second polymer has good compatibility with the binder PVDF, which can help PVDF to disperse. At the same time, the second polymer itself also has adhesiveness and is not easy to crack during the coating and drying process of the electrode. The b in the structural formula I represents a block copolymer.

[0022] The first solvent is N-methylpyrrolidone (NMP). When the first polymer and the second polymer are dissolved in the first solvent, the dissolution process can be promoted by heating. Optionally, the temperature can be heated to 60-100° C., for example, heated to 85° C.

[0023] In step 2, the added amine compound is one of isopropanolamine, N-methyldiethanolamine, ethanolamine or isobutanolamine. The mass ratio of the amine compound to the first solvent is 0.1 to 5:100. Optionally, the mass ratio of the amine compound to the first solvent is 2 to 4:100. After adding an excess of the amine compound and neutralizing the catalyst, the pH can be adjusted to alkaline (pH above 10).

[0024] In the present application, after dissolving the first polymer and the second polymer in the first solvent, a modifier and a catalyst are added for in-situ modification. The modified first polymer and the second polymer act together as anti-cracking agents. The first polymer and the second polymer cooperate with each other and have a better anti-cracking effect.

[0025] The first polymer and the second polymer form a network structure through intermolecular forces, and the first polymer and the second polymer are both very compatible with aluminum foil and can better adhere to the surface of the aluminum foil without cracking. The first polymer and the second polymer are also very compatible with lithium iron phosphate in the positive electrode slurry, which is conducive to maintaining excellent battery performance.

[0026] Small molecule amine compounds can not only adjust the pH of the anti-cracking agent, but also the excess small molecule amines contain amino groups and hydroxyl groups on the surface, which have good wettability to lithium iron phosphate positive electrode and carbon conductive agent, and can improve the dispersion viscosity of the positive electrode slurry and reduce the surface tension of the slurry. During the electrode baking process, the small molecule amines form an azeotrope with the first solvent NMP, avoiding the rapid volatilization of NMP and the formation of pits on the electrode surface, thereby obtaining a electrode with a smooth surface after drying.

[0027] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.

[0028] Optionally, the mass ratio of the first polymer to the first solvent is 5 to 10:100.

[0029] Optionally, the mass ratio of the second polymer to the first solvent is 2 to 8:100.

[0030] Optionally, the mass ratio of the modifier to the first solvent is 0.5 to 5:100.

[0031] The modifier is one of maleic anhydride or maleic anhydride derivatives. The maleic anhydride derivative is one of maleic acid, bismaleic anhydride (formed by condensation of two maleic anhydride molecules, having a bis-anhydride structure), maleic anhydride ester (formed by reaction of maleic anhydride and alcohol), maleic anhydride amide (formed by reaction of maleic anhydride and amines), and maleic anhydride copolymer (formed by copolymerization of maleic anhydride and other monomers).

[0032] Optionally, the mass ratio of the catalyst to the first solvent is 0.1 to 1:100.

[0033] Optionally, the content (mass percentage) of methyl methacrylate in the second polymer is 8% to 65%. Further preferably, the content of methyl methacrylate in the second polymer is 10% to 50%. Further preferably, the content of methyl methacrylate in the second polymer is 20% to 30%.

[0034] Optionally, the weight average molecular weight of the second polymer is 5,000 to 120,000.

[0035] Optionally, the reaction time of step 1 is 8 to 24 hours; the reaction time of step 2 is 1 to 4 hours.

[0036] Optionally, the viscosity of the first polymer is 4-50 mPa·s, and the viscosity of the second polymer is 300-1000 mPa·s. Optionally, the viscosity of the first polymer is 4-50 mPa·s, and the viscosity of the second polymer is 300-700 mPa·s.

[0037] In the present application, the first polymer and the second polymer are both solids, and their viscosity is the viscosity of a dilute solution prepared by dissolving the first polymer and the second polymer in a solvent. Since the first polymer and the second polymer are used in the slurry of lithium-ion batteries, the viscosity of the first polymer and the second polymer is selected to be moderate and used in the positive electrode slurry, so that the positive electrode slurry has a suitable viscosity, and the viscosity is relatively stable and not easy to change over time.

[0038] The viscosity of the first polymer is the viscosity of an 8% by mass NMP solution of the first polymer measured at 25° C. The viscosity of the second polymer is the viscosity of a 5% by mass NMP solution of the second polymer measured at 25° C.

[0039] The present application also provides a lithium ion battery anti-cracking agent, which is prepared by the preparation method.

[0040] The present application also provides a positive electrode slurry for a lithium-ion battery, wherein the raw materials of the positive electrode slurry for a lithium-ion battery are composed of the following parts by weight:

[0041]

[0042] Optionally, the raw materials of the lithium-ion battery positive electrode slurry are composed of the following parts by weight:

[0043]

[0044] The lithium ion battery anti-cracking agent provided in the present application, with an addition amount of less than 0.5%, can make the single surface density reach 200g / m 2 , which can meet the needs of high energy density lithium-ion batteries.

[0045] The lithium-ion battery anti-cracking agent provided in the present application can keep the battery pole piece intact and crack-free at a high surface density at a relatively low addition amount, thus meeting the requirements of high energy density lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Thermogravimetric analysis of the polymer solution prepared in Example 1;

[0047] Figure 2 This is a thermogravimetric analysis diagram of polyvinyl butyral of Comparative Example 1;

[0048] Figure 3 The polymer solution prepared in Example 1 was coated on aluminum foil for CV curve test;

[0049] Figure 4 It is the electrode sheet resistance test diagram of application example 1-A and application example 1-B;

[0050] Figure 5 This is a photo of the front coating of Application Example 1-C group;

[0051] Figure 6 This is a photo of the reverse coating of Application Example 1-C group;

[0052] Figure 7 This is a photo of the front coating of the comparative application example 2-D group;

[0053] Figure 8 This is a photo of the front coating of the comparative application example 2-D group;

[0054] Fig. 9 This is a photo of the front side of the application example 1-C group after rolling after coating;

[0055] Fig.10 This is a photo of the reverse side of Application Example 1-C group after roller pressing. DETAILED DESCRIPTION

[0056] Example 1

[0057] Under nitrogen protection, 100 parts of NMP first solvent (parts by weight, the same for the other raw materials) were weighed, 8 parts of polyvinyl butyral (Kuraray brand B30H, the viscosity of this brand of polyvinyl butyral is 4mPa·s, which is the viscosity of NMP solution with a mass fraction of 8% polyvinyl butyral at 25°C, and the hydroxyl content of this brand of polyvinyl butyral is 19%) were added, 5 parts of methyl methacrylate-butyl acrylate triblock polymer (Kuraray LA 2330 brand, the viscosity of the methyl methacrylate-butyl acrylate triblock polymer of this brand is 350mPa·s, which is the viscosity of the NMP solution of 5% methyl methacrylate-butyl acrylate triblock polymer at 25°C, and the methyl methacrylate content of the methyl methacrylate-butyl acrylate triblock polymer of this brand is 35%), heated to 85°C, dissolved for 4 hours, and then 4 parts of maleic anhydride and 1 part of p-toluenesulfonic acid were added to react for 8 hours. After the reaction was completed, it was cooled to 35°C, 4 parts of isobutanolamine were added, and the reaction was carried out for 4 hours. The polymer solution obtained after the reaction was completed was the lithium ion battery anti-cracking agent.

[0058] After the polymer solution prepared in Example 1 was dried, thermogravimetric analysis was performed (crucible type: alumina, atmosphere: nitrogen). Figure 1 As shown, the decomposition temperature is 320°C.

[0059] The polymer solution prepared in Example 1 was coated on aluminum foil and a CV curve test was performed. The test results are shown in Figure 3 As shown, it can be seen that the polymer has good electrochemical stability and is stable at 4.8V without decomposition. Figure 3 In the above, the third paragraph refers to the third cycle, the fourth paragraph refers to the fourth cycle, the fifth paragraph refers to the fifth cycle, and the sixth paragraph refers to the sixth cycle. Figure 3 Different colors are used to mark different cycles. The descriptions of the different colored lines in the lower right corner are paragraph 3, paragraph 4, paragraph 5, and paragraph 6 from top to bottom.

[0060] Example 2

[0061] Under nitrogen protection, 100 parts of NMP first solvent (parts by weight, the same for the other raw materials) were weighed, 10 parts of polyvinyl butyral (Kuraray brand B16H, the viscosity of this brand of polyvinyl butyral is 10 mPa·s, which is the viscosity of NMP solution with a mass fraction of 8% polyvinyl butyral at 25°C, and the hydroxyl content of this brand of polyvinyl butyral is 21%), 8 parts of methyl methacrylate-butyl acrylate triblock polymer (Kuraray LA 2330 brand, the viscosity of the methyl methacrylate-butyl acrylate triblock polymer of this brand is 350mPa·s, which is the viscosity of the NMP solution of 5% methyl methacrylate-butyl acrylate triblock polymer at 25°C, and the methyl methacrylate content of this brand of methyl methacrylate-butyl acrylate triblock polymer is 35%), heated to 85°C, dissolved for 4 hours, then added 5 parts of maleic anhydride and 1 part of p-toluenesulfonic acid, and reacted for 8 hours. After the reaction is completed, it is cooled to 35°C, 4 parts of isopropanolamine are added, and the reaction is carried out for 4 hours. The polymer solution obtained after the reaction is completed is the lithium ion battery anti-cracking agent.

[0062] Example 3

[0063] Under nitrogen protection, 100 parts of NMP first solvent (parts by weight, the same for the other raw materials) were weighed, 10 parts of polyvinyl butyral (Kuraray brand B16H, the viscosity of this brand of polyvinyl butyral is 10mPa·s, which is the viscosity of NMP solution with a mass fraction of 8% polyvinyl butyral at 25°C, and the hydroxyl content of this brand of polyvinyl butyral is 21%), 5 parts of methyl methacrylate-butyl acrylate triblock polymer (Kuraray LA 3320 brand, the viscosity of the methyl methacrylate-butyl acrylate triblock polymer of this brand is 680mPa·s, which is the viscosity of the NMP solution of 5% methyl methacrylate-butyl acrylate triblock polymer at 25°C, and the methyl methacrylate content of this brand of methyl methacrylate-butyl acrylate triblock polymer is 56%), heated to 85°C, dissolved for 4 hours, then added 5 parts of maleic anhydride and 1 part of p-toluenesulfonic acid, and reacted for 8 hours. After the reaction is completed, it is cooled to 35°C, 4 parts of ethanolamine are added, and the reaction is carried out for 4 hours. The polymer solution obtained after the reaction is completed is the lithium ion battery anti-cracking agent.

[0064] Comparative Example 1

[0065] 8 parts of polyvinyl butyral (same as in Example 1) were dissolved in 100 parts of NMP (parts by weight) and subjected to thermogravimetric analysis. Figure 2 As shown, the decomposition temperature starts at about 190°C, there is weight loss within 200°C, it decomposes rapidly at 330°C, and is completely decomposed at 480°C.

[0066] Application Example 1

[0067] The polymer solution obtained in Example 1 was used to prepare positive electrode slurry in a weight ratio of lithium iron phosphate: carbon black: binder PVDF: polymer solution: NMP = 97:1:2.5:0.5:40. The solid content, viscosity, storage viscosity, fineness of the positive electrode slurry, the appearance of thick-coated pole pieces and the rolling surface density were tested, and the battery was disassembled after full charge.

[0068] Comparative application example 1

[0069] Without using modified polymer, the positive electrode slurry was prepared in a weight ratio of lithium iron phosphate: carbon black: binder PVDF: NMP = 97:1:2.5:40. The solid content, viscosity, storage viscosity, fineness of the positive electrode slurry, the appearance of the thick-coated electrode and the rolling surface density were tested, and the battery was disassembled after full charge.

[0070] Comparative Application Example 2

[0071] The polyvinyl butyral solution of Comparative Example 1 was used to prepare positive electrode slurry in a weight ratio of lithium iron phosphate: carbon black: binder PVDF: polyvinyl butyral solution: NMP = 97:1:2.5:0.5:40. The solid content, viscosity, storage viscosity, fineness of the positive electrode slurry, the appearance of thick-coated pole pieces and the rolling surface density were tested, and the fully charged battery was disassembled.

[0072] Performance Data

[0073] The characterization results of the solid content, viscosity and fineness of the positive electrode slurry of Application Example 1, Comparative Application Example 1 and Comparative Application Example 2 are shown in Table 1.

[0074] Table 1

[0075] performance Application Example 1 Comparative application example 1 Comparative Application Example 2 Solid content% 60.19 65.91 65.38 Viscosity mPa·s 3583 6437 4417 Fineness (particles) μm 45 40 40

[0076] The static viscosity test results of Application Example 1, Comparative Application Example 1 and Comparative Application Example 2 are shown in Table 2, and the unit of viscosity is mPa·s.

[0077] Table 2

[0078]

[0079]

[0080] It can be seen from the viscosity test results in Table 1 and the static viscosity test results in Table 2 that the polymer solution of Experimental Example 1 used in Application Example 1 has lower slurry viscosity and placement viscosity than that of using no polymer or using PVB.

[0081] The additive content, double-sided coating density and coating method corresponding to Comparative Application Example 1-A, Application Example 1-B, Application Example 1-C and Comparative Application Example 2-D are shown in Table 3.

[0082] Table 3

[0083]

[0084] See also Figure 4 As shown, comparing Application Example 1-A group with Application Example 1-B group, Application Example 1-B uses the polymer solution of Example 1 and has lower electrode sheet resistance.

[0085] The coating appearance of application example 1-C group and comparative application example 2-D group are shown in Figure 5 , Figure 6 , Figure 7 , Figure 8 As shown, the double-sided density of group C is 520g / m 2 , double-sided density of group D: 470g / m 2 .Depend on Figure 5 , Figure 6 It can be seen that the double-sided density of application example 1-C group reaches 520g / m 2 , no cracks in the middle, Figure 7 , Figure 8 It can be seen that the double-sided density of the comparative application example 2-D is only 470g / m 2 , there are cracks on the edges and in the middle.

[0086] See also Fig. 9 , Fig.10 As shown, after rolling in Application Example 1-C, there is no cracking on the front and back sides, indicating that the polymer solution prepared in Example 1 has an obvious pole piece toughening effect.

[0087] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0088] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a lithium ion battery anti-cracking agent, characterized in that: Included under nitrogen protection: Step 1, dissolving the first polymer, the second polymer and the modifier in the first solvent, reacting at 60-100° C. for 4-48 hours under the action of a catalyst; Step 2, after the reaction in step 1 is completed, the temperature is lowered to below 40° C., an amine compound is added, and the reaction is carried out for 0.5 to 8 hours to obtain the lithium ion battery anti-cracking agent; The first polymer is polyvinyl butyral, and the hydroxyl content of polyvinyl butyral is 18-21%; The second polymer is a triblock polymer as shown in structural formula I, and the content of methyl methacrylate in the second polymer is 8% to 65%; Structural Formula I The modifier is maleic anhydride or a maleic anhydride derivative; The catalyst is one of p-toluenesulfonic acid, hydrochloric acid and sulfuric acid.

2. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The mass ratio of the first polymer to the first solvent is 5 to 10:

100.

3. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The mass ratio of the second polymer to the first solvent is 2 to 8:

100.

4. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The mass ratio of the modifier to the first solvent is 0.5 to 5:

100.

5. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The mass ratio of the catalyst to the first solvent is 0.1 to 1:

100.

6. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The weight average molecular weight of the second polymer is 5,000 to 120,000.

7. The method for preparing the lithium ion battery anti-cracking agent according to claim 1, characterized in that: The reaction time of step 1 is 8 to 24 hours; the reaction time of step 2 is 1 to 4 hours.

8. A lithium ion battery anti-cracking agent, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.

9. A lithium-ion battery positive electrode slurry, characterized in that: The raw materials weight parts of the lithium ion battery positive electrode slurry are as follows:

Citation Information

Patent Citations

  • Conductive paste and mixture paste for lithium ion battery positive electrode

    CN107528067A

  • Anti-cracking agent for lithium ion battery as well as preparation method and application of anti-cracking agent

    CN118652362A

  • Catalyst paste composition for fuel cell, catalyst ink composition, catalyst layer or water repellent layer, electrode membrane assembly, and fuel cell

    JP2014216204A

  • Liquid crystal sealant composition containing block copolymer

    JP2022165527A

  • Hot melt composition for sticking road surface display material, and color changing hot melt composition for sticking road surface display material

    JP2023059831A

Cited By

  • Anode slurry dispersing, compacting and anti-cracking auxiliary agent for lithium battery and preparation method thereof

    CN121394408A

  • Anti-cracking auxiliary agent for lithium ion battery negative electrode and preparation method and application of anti-cracking auxiliary agent

    CN121554749A

  • Anti-cracking additive for lithium ion battery negative electrode and preparation method and application thereof

    CN121554749B